Basic Analysis of the National Biotechnology Policy 2.0 Survey (SDB 2.0): An Overview - Sekaran, Sareniya; Mohamad Fauzi, Siti Fatimah Zaharah; Abd Aziz, Suraini; Phang , Lai Yee; Salleh, Madihah (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates public perceptions and awareness of biotechnology in Malaysia, focusing on the impact of the National Biotechnology Policy 2.0 (NBP 2.0). Conducted through a structured survey administered via Google Forms, the research gathered responses from 200 respondents, including researchers, industry professionals, policymakers, and educators. Results indicate significant awareness and positive attitudes towards biotechnological innovations across key sectors outlined by NBP 2.0: agricultural biotechnology, healthcare, and industrial biotechnology. Specifically, 85% of respondents recognized the potential of biotechnology to enhance agricultural productivity and food security. In healthcare, 78% acknowledged biotechnology’s role in advancing medical treatments and wellness solutions. Additionally, 72% of respondents viewed industrial biotechnology as crucial for economic sustainability. Concerns regarding ethical implications and regulatory frameworks were also noted, reflecting a nuanced understanding across diverse demographic profiles. Quantitative and qualitative analyses underscore the policy’s potential to address global challenges and inform evidence-based decision-making to foster public trust in biotechnology advancements.